An Evaluation of Pass/Fail Decisions through Norm- and Criterion-Referenced Assessments - Selahattin Gelbal; Ismail Cuhadar (International Journal of Assessment Tools in Education)
The institutions in education use various assessment methods to decide on the proficiency levels of students in a particular construct. This study investigated whether the decisions differed based on the type of assessment: norm- and criterion-referenced assessment. An achievement test with 20 multiple-choice items was administered to 107 students in guidance and psychological counseling department to assess their mastery in the course of measurement and evaluation. First, the raw scores were transformed into T-scores for the decisions from norm-referenced assessments. Two decisions were made to classify students as passed/failed comparing each student’s T-score with two common cutoffs in education: 50 and 60. Second, two standard-setting methods (i.e., Angoff and Nedelsky) were conducted to get two cut scores for the criterion-referenced assessment with the help of experts in measurement and evaluation. Two more decisions were made on the classification of students into pass/fail group by comparing the raw scores and the cut scores from two standard-setting methods. The proportions of students in pass/fail categories were found to be statistically different across each pair of four decisions from norm- and criterion-referenced assessments. Cohen’s Kappa showed that the decisions based on Nedelsky method indicated a moderate agreement with the pass/fail decisions from the students’ semester scores in measurement and evaluation while the other three decisions showed a lower agreement. Therefore, the criterion-referenced assessment with Nedelsky method might be considered in making pass/fail decisions in education due to its criterion validity from the agreement with the semester scores.